Color image with Dim regions Enhancement Using Modified Histogram Equalization Algorithm - Kareem, Hana H (Al-Nahrain Journal of Science, 2012)
In this paper the color images with dim regions have been enhanced by using modified histogram equalization (MHE) algorithm. This technique uses the lightness component in YIQ color space is transformed using sigmoid function, then the traditional histogram equalization (HE) method is applied on Y component. A relationship between the mean and the average of standard deviation for images have been done for images with dim regions and select regions in these images, as well the histogram to examine the efficiency of the work. The result of MHE method has been compared with the result of other method like Adaptive Integrated Neighborhood Dependent Approach for Nonlinear Enhancement of Color Images (AINDANE) and traditional histogram equalization algorithm. All algorithms has implemented using program (Matlab). The suggestion algorithm appeared good enhancement for both regions with moderate and low lightness (dim region) compared with others algorithms.